2018
DOI: 10.1007/s00405-018-5203-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings on 18-FDG PET–CT in head and neck cancer. A retrospective case-control study of incidental findings on 18-FDG PET–CT in patients with head and neck cancer

Abstract: PurposeUse of 18-FDG PET–CT is increasing in patients with head and neck cancer, enabling the identification of metastases or synchronous malignancies, but also ‘incidental’ disease. We aimed to establish the rate of ‘incidental’ findings resulting from 18-FDG PET-specific imaging, that would not have been otherwise identified on other imaging, in patients with head and neck cancer undergoing staging or surveillance of disease.Methods18-FDG PET–CT was performed for investigation or surveillance. Case notes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
2
5
1
Order By: Relevance
“…Wang et al investigated FDG‐PET/CT restaging examinations for different cancers and reported an overall rate of 8% proven synchronous second primaries 43 . For head and neck cancer, Britt et al and Casselden et al found synchronous second primaries in 3.2% (3/93) and 4.1% (12/293), respectively 44,45 . In our study, a second primary was found in 6.1% (6/96) of all PET examinations.…”
Section: Discussionsupporting
confidence: 57%
“…Wang et al investigated FDG‐PET/CT restaging examinations for different cancers and reported an overall rate of 8% proven synchronous second primaries 43 . For head and neck cancer, Britt et al and Casselden et al found synchronous second primaries in 3.2% (3/93) and 4.1% (12/293), respectively 44,45 . In our study, a second primary was found in 6.1% (6/96) of all PET examinations.…”
Section: Discussionsupporting
confidence: 57%
“…The field of view in the oral and maxillofacial region often includes a region from the base of the brain to the apex of the lung, and thus oral radiologists need to take care to observe adjacent regions in the images. Indeed, many incidental findings have been described in previous reports (6)(7)(8)(9)(19)(20)(21). The thyroid gland should be focused upon because its entirety is frequently included in CT images of the oral and maxillofacial region.…”
Section: Discussionmentioning
confidence: 97%
“…With the development of imaging modalities in recent years, there has been an increase in the identification of incidental lesions on images obtained by CT and MRI, as advanced imaging modalities (6)(7)(8)(9)(19)(20)(21). In particular, CT machines are maintained at many facilities, and it is possible to obtain more detailed diagnoses by CT immediately after lesions are suspected on plain radiographs of the oral and maxillofacial region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to the best of our knowledge, no studies have investigated incidental FDG uptake in the oropharynx specifically. Incidental PET uptake in the head and neck was analysed in 16 papers and was shown to occur in 13.8% of scans on average (Table 4) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The presence of PET incidentalomas was associated with a significant increase in time to commencement of treatment [14].…”
Section: Discussionmentioning
confidence: 99%